PENGARUH PEMBERIAN BEBERAPA JENIS PUPUK TERHADAP HASIL BROKOLI (Brassica oleracea var. Italica) - Herni F. Wani; Pemmy Tumewu; Stanley A.F. Walingkas; Maria G.M. Polii; Meity R. Rantung; Paula C.H Supit (EUGENIA, 2024)
The research aims to determine the effect of several types of fertilizer on broccoli crop yields, carried out from June - August 2023 in Kakaskasen Village, Tomohon City, North Sulawesi Province. The research used a Randomized Block Design (RAK) method with 5 (treatment) types of fertilizer. Treatments consisted of: P0 (No fertilization), P1 Phonska fertilizer 75kg/ha and urea 50kg/ha, P2 Chicken manure 20 tons/ha, P3 Goat manure 20 tons/ha, P4 Pig manure 20 tons/ha and all treatments Using manure is applied 3 days before transplanting, phonska and urea fertilizer are applied 1 week after planting. The variables observed were plant height (cm), number of leaves (strands), crop diameter (cm), crop wet weight (g). Data were analyzed using analysis of variance (ANOVA) and if there was a significant effect, it was continued with the BNT test at the 5% level. The research results show that several types of fertilizer affect the yield of broccoli plants. Providing 20 tonnes/ha of goat manure and 20 tonnes/ha of pig manure gave the best broccoli yields. Keywords : fertilization, broccoli, brassica